Implementing contemporary issues through curriculum development, teaching models and curriculum design for teaching institutes in Nigeria - S. Adiaha, Monday; I. Anabe, Momoh; A. Ndifon, Mary; I. Udom, Grace; U. Ocheje, David (SPC Journal of Education, 2019)
The paper investigated contemporary issues in Nigeria through curriculum development and teaching models at various levels of education. In this research the researchers found that curriculum designing is conducted stage by stage at all levels of education. It was found out that some of the model presented the process stage to be more important than the objectives. Other models puts objectives to be the most important feature of curriculum design. All models presented stress the importance of considering a variety of factors affecting the society in which the curriculum is to be implemented, as curriculum is meant to solve the problem of the society in which it is developed.Â Â Â